Skilled migration: a structural determinant of health. Issue 4 (28th November 2019) - Vandenberg, Miriam; Fan, Si; Cooling, Nick; Harris, Keith M.; Chin, James
Abstract : Purpose: Attention on world migration has mostly focused on economic and inter-personal impacts, leaving a large gap in our understanding of how migration can affect migrants' health. The purpose of this paper is to illustrate how the interdependent experiences of skilled migrants, as they undertake the latter part of their journey of skilled migration and resettle into their adopted homeland, can be conceptualised as a structural determinant of health. Design/methodology/approach: In this qualitative study, semi-structured interviews collected data on skilled migrants' experiences, including health impacts, related to their migration to Tasmania, Australia. A social determinants of health (SDOH) framework and Bourdieu's theory of practice were applied to interpret the findings. Findings: In total, 16 skilled migrants, from several nations and occupations, provided wide-ranging accounts of social inclusion and exclusion, and frequently reported experiencing psychological stress. There were also some reports of improved mental health. The migration process shapes life's chances and choices. Many migrants reported access to important social, economic and cultural resources, however, good health was also impeded by equally significant systemic barriers. Research limitations/implications: The sample is small and confined to a geographically isolated location, and did not include all types of skilled migrants. Practical implications: Countries resettling skilled migrants should modify systems to promote rather than inhibit wellbeing, e.g. government and industry partnerships to facilitate employability and enhance access to supportive information about the migration process. Originality/value: This is the first known study to link Bourdieu's theory to SDOH relevant to skilled migrants. This approach helped reveal the prominence of structural factors beyond the control of migrants but potentially modifiable by the host country. This study illustrates the importance of examining both positive and negative health outcomes associated with migration, and how these factors relate to theory and policy.